Dampak sosial perkawinan di bawah umur bagi kehidupan masyarakat desa Kunjorowesi Kecamatan Ngoro Kabupaten Mojokerto - Yuniastuti Yuniastuti (Jurnal Teori dan Praksis Pembelajaran IPS, 2017)
In the Village Kunjorowesi, District Ngoro, Mojokerto there are many do underage marriage, from the initial data that researchers get before this study conducted by informan, and He said in terms of education alone, many children graduated from elementary school especially female do not continue to junior high school because She helping Her parents and married by parents, from the data alone can be seen that the very low awareness of the community both from the understanding of the importance of education and the harmful effects of marriage underage, Researchers also found a child who was aged around 17 years but has two times divorcee and have children from both marriages. This research will use qualitative research with case studies as formulated (Robert K. Yin, 2008), case study research is a method that refers to research that has elements of how and why on the main questions of his research and examining contemporary issues and the least chance of researchers in controlling cases examined.Keyworda: Social Impact, Marriage, Social Life http://dx.doi.org/10.17977/um022v2i12017p031